2018
DOI: 10.1155/2018/1489132
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Serum Nitric Oxide with Vitamin D and Other Metabolic Factors in Apparently Healthy Adolescents

Abstract: Introduction Nitric oxide (NOx) is an important biomolecule which interacts with other molecules including 25(OH)D to mediate various metabolic pathways. Interactions and associations of NOx with 25(OH)D have been well studied both in vitro and in vivo, yet associations in apparently healthy adolescents have never been studied. Methods A total of 740 (245 boys and 495 girls) apparently healthy Saudi adolescents aged 10-17 years were included in this cross-sectional study, to determine the associations of NOx w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…On the flip side, decreased vitamin D concentration has been linked to elevated levels of NO. The protective efficacy of this vitamin against endothelial dysfunction as well as cardiovascular system could also be explained through this inverse relationship between NO and S5OHD levels [45]. Further, glutathione (GSH) presence in astrocytes may be associated with nitrogen and oxygen reactive species eliminating procedure (such as NO) [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…On the flip side, decreased vitamin D concentration has been linked to elevated levels of NO. The protective efficacy of this vitamin against endothelial dysfunction as well as cardiovascular system could also be explained through this inverse relationship between NO and S5OHD levels [45]. Further, glutathione (GSH) presence in astrocytes may be associated with nitrogen and oxygen reactive species eliminating procedure (such as NO) [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Togha and coworkers demonstrated that chronic migraineurs had lower total antioxidant non-enzymatic capacity and higher ROS levels than EM patients (50). Physiological VitD level decreases intracellular oxidative stress-related activities, up-regulating the expression of several genes implicated in mitochondrial activity, defense against oxidative burst and aging, and particularly of the nuclear factor erythroid-2(Nf-E2)-related factor and of Klotho (43,(53)(54)(55)(56)(57) Obesity is a pro-in ammatory condition and bears the potential to intensify neurovascular in ammation.…”
Section: Discussionmentioning
confidence: 99%
“…As a neurosteroid, vitamin D plays a vital role in preventing vascular injury through the mechanism of inhibiting the renin-angiotensin-aldosterone system and atherogenesis [7], lowering blood pressure, reduction in endothelial dysfunction [13], and neuroprotective actions in stroke [14]. Accumulating data have supported the hypothesis lower 25(OH)D level was associated with ischemic stroke, higher mortality and poor outcome [15][16][17][18][19][20][21][22][23][24][25][26], and a higher vitamin D was linked to a decreased risk of cerebrovascular disease [27].…”
Section: Discussionmentioning
confidence: 99%